Identity management in healthcare using blockchain technology - Santos, João Pedro Nunes dos (2018)
Bitcoin served as the catalyst for creating a solution to secure digital transactions without requiring a trusted third party to be involved. To solve this problem, the mechanisms now associated with a Blockchain were conceptualized and implemented to serve as the backbone for the Bitcoin network. More specifically, it was used as a security tool making Bitcoin a more transparent and reliable form of cash, a digital cryptographic currency. Even tough Bitcoin ended up not fulfilling its intended purpose as a currency, the Blockchain technology has enabled further avenues for innovation and creativity. Blockchain has since been used as the backbone for various cryptocurrencies networks. Some implementations of this technology allow the execution of code, also known as ”smart contracts”. Smart contracts are executed in an autonomous manner, with no human intervention. These can be used to solve a new set of problems due to their transparent behavior, lack of human intervention and distributed nature. Blockchain technology allows the creation of systems that introduce a number of benefits over traditional data handling used in today’s Healthcare Information Systems. Costs and risks associated with these systems can be reduced and information can become transparent and trustworthy to all participants. The Hyperledger Fabric Network with true private transactions and advanced security mechanisms was used to serve as the basis for the system proposed in this dissertation. Moreover, a client application was also created that interacts with smart contracts to manipulate the ledger. The work discussed in this dissertation shows that a Blockchain system based on Hyperledger Fabric is suitable for managing patients identity, in Healthcare. Even tough the feature set of this Blockchain is very focused in privacy and security, some additional measures regarding confidentiality of data had to be implemented. Regardless, a system was built successfully that met the requirements. The implementation of this system would provide transparency, immutability and additional security for patients and medical staff alike; Sumário: Gestão de Identidade nos Serviços de Saúde Utilizando Tecnologia Blockchain A criptomoeda Bitcoin foi essencial para criar uma solução para transacções digitais seguras, sem requerer a participação de um terceiro interveniente fidedigno para ambas as partes. Para resolver este problema, os mecanismos que hoje são associados com a tecnologia Blockchain foram concebidos e implementados para servir como base para a rede da Bitcoin. Mais especificamente, esta foi utilizada como um mecanismo de segurança, de forma a tornar a Bitcoin uma forma de dinheiro mais transparente e estável, uma moeda criptográfica. Mesmo que a Bitcoin não tenha conseguido cumprir o seu propósito original, a tecnologia Blockchain despoletou novas inovações e permitiu maior criatividade. A Blockchain tem sido, desde então, a base tecnológica de várias criptomoedas. Algumas implementações desta tecnologia permitem a execução de código de uma forma autónoma exactamente como foi programado, sem intervenção humana. Habitualmente chamados smart contracts, estes podem ser usados para resolver um novo conjunto de problemas devido ao seu comportamento transparente, ausência de intervenção humana e devido à sua natureza distribuida. A Blockchain é uma tecnologia que permite a criação de sistemas que introduzem um conjunto de beneficios em relação aos sistemas tradicionais de armazenamento de dados utilizados nos serviços de saúde. Custos e riscos associados a estes sistemas podem ser reduzidos e a informação pode ser mais transparente e fidedigna para todos os participantes. A rede Hyperledger Fabric com transacções privadas e mecanismos avançados de segurança foi usada como base para a criação do sistema proposto nesta dissertação. Adicionalmente, uma aplicação foi criada que usa smart contracts para manipular o ledger da Blockchain. O trabalho apresentado nesta dissertação mostra que um sistema baseado em Blockchain, neste caso em Hyperledger Fabric, é adequado a gerir a identidade de utentes, em organizações prestadoras de cuidados de saúde. Apesar das funcionalidades apresentadas por esta plataforma serem focadas em privacidade e segurança, algumas medidas adicionais em torno da confidencialidade dos dados tiveram de ser implementadas. Independentemente disso, o sistema foi construido com sucesso e conseguiu cumprir os requerimentos que foram definidos. A implementação deste sistema em serviços de saúde traria tranparência, imutabilidade e segurança adicional para utentes e profissionais de saúde.